2020
DOI: 10.1021/acsomega.0c02854
|View full text |Cite
|
Sign up to set email alerts
|

Valorizing Plastic-Contaminated Waste Streams through the Catalytic Hydrothermal Processing of Polypropylene with Lignocellulose

Abstract: Food waste is a promising resource for the production of fuels and chemicals. However, increasing plastic contamination has a large impact on the efficiency of conversion for the more established biological routes such as anaerobic digestion or fermentation. Here, we assessed a novel route through the hydrothermal liquefaction (HTL) of a model waste (pistachio hulls) and polypropylene (PP). Pure pistachio hulls gave a biocrude yield of 34% (w/w), though this reduced to 16% (w/w) on the addition of 50% PP in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“… Oil yield obtained with various catalysts used for converting plastics into fuels (aluminosilicate: Al 2 O 5 Si; bentonite clay: Al 2 H 2 Na 2 O 13 Si 4 ) [160c,162c,166,170] …”
Section: Hydrothermal Liquefaction Of Plastic Waste Into Fuelsmentioning
confidence: 99%
“… Oil yield obtained with various catalysts used for converting plastics into fuels (aluminosilicate: Al 2 O 5 Si; bentonite clay: Al 2 H 2 Na 2 O 13 Si 4 ) [160c,162c,166,170] …”
Section: Hydrothermal Liquefaction Of Plastic Waste Into Fuelsmentioning
confidence: 99%
“…Mariculture enterprises can be severely impacted by microplastics because farming sites are usually located in sheltered areas, where microplastics often accumulate . Microplastics are reported to adhere to external appendages of planktonic organisms and the gills of molluscs and shellfish. , Microplastics can be taken up directly via ingestion, either through filtration or scavenging. Higher loads of microplastics cause low lysosomal stability, increased cellular demand, depleted energy storage, and increased mortality in oysters .…”
Section: Examples Of Symbiotic Engineering Processesmentioning
confidence: 99%
“…The highest bio-crude oil yield from fast HTL was as high as the highest yields from isothermal HTL (28-30 wt.% at 300-400 • C). Recently, a study on co-HTL of pistachio hulls and polypropylene (PP) showed that HTL can be a promising method for valorization of food waste and associated plastic materials with the addition of hydrogen donor solvents and catalysts under typical conditions (<350 • C) (Hongthong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%